Đặc điểm thạch quyển khu vực Biển Đông, quan hệ của nó với dị thường dòng nhiệt - Toàn, Đinh Văn; Bắc, Trịnh Việt (Vietnam Journal of Earth Sciences, 2018)
About the Litttosphere in the East Sea region and its relation with heat flow anomalies